2018
DOI: 10.5546/aap.2018.eng.e508
|View full text |Cite
|
Sign up to set email alerts
|

Physical growth in young Chilean football players: Proposal of percentiles based on chronological and biological age

Abstract: These youth showed different physical growth patterns compared to the CDC-2012 standard. Their assessment reflects better explanatory percentages for biological age than for chronological age. The proposed percentiles may be an alternative to keep track of the physical growth patterns of young football players in sports settings in the short, medium, and long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…To our knowledge, few studies have been identified that propose referential values in young soccer players. However, these studies do not cover a wide age range, usually, they have been limited to some physical tests (Lesinski et al, 2020;Selmi et al, 2020;Romero-Caballero et al, 2021;Smpokos et al, 2022), or have been proposed to separately analyze physical growth and BC (Carrasco-López et al, 2018;Carrasco-López et al, 2021), which limits their use and application.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, few studies have been identified that propose referential values in young soccer players. However, these studies do not cover a wide age range, usually, they have been limited to some physical tests (Lesinski et al, 2020;Selmi et al, 2020;Romero-Caballero et al, 2021;Smpokos et al, 2022), or have been proposed to separately analyze physical growth and BC (Carrasco-López et al, 2018;Carrasco-López et al, 2021), which limits their use and application.…”
Section: Introductionmentioning
confidence: 99%